Research and innovation priorities for enabling legume scaling for development outcomes in Malawi - Johnston, Angharad; Varley, Ciara; Recha, John W.M.; Longwe, Kareem; Ndlovu, Noel; Munthali, Timalizge W; Silumesi, Mwala; Kalumo, Decolius; Mushangure, Remeredzai O; Kaonga, Tione P; Kinkese, Theresa; Breen, Caitlin; et al. (University of Galway and IITA, 2024)
Legumes are critical to agriculture, food security and economic development in Malawi. The EUfunded LEG4DEV project is conducting research & innovation activities with scaling partners in Malawi to enable them to more e6ectively scale legumes for development outcomes (productivity, health & nutrition, sustainability, livelihood security). Following an intensive schedule of bilateral meetings with stakeholders and potential scaling partners in Malawi, the LEG4DEV project organised and ran a “Legumes for Development” multistakeholder research prioritisation workshop on December 09th 2022, in Lilongwe, Malawi (Annex 1). The LEG4DEV Multistakeholder workshop was held at Lilongwe’s Sunbird Capital Hotel and was opened by Mr. David Kamangira from the Department of Agricultural Research Services (DARS), on behalf of the Malawi Ministry of Agriculture. He highlighted the importance of legume scaling to national development goals of Malawi in relation to agricultural productivity, health & nutrition, sustainability and livelihoods. The LEG4DEV Multistakeholder Malawi workshop was attended by 82 attendees from government, research organisations, universities, donors, NGOs, farmers organisations and companies (Annex 2). The workshop was organised around the six work packages of the LEG4DEV project where workshop participants worked in interdisciplinary teams to identify their highest priority research questions (both technical and policy/institutional) that the LEG4DEV project research could focus on in Malawi to better enable legume scaling at the national level.